Working with Industry: What Is the Conflict? - Marcello, Peter W. (Clinics in Colon and Rectal Surgery, 2013)
The relationship between medicine and industry has always shared conflicts. There are obvious benefits to these relationships and inherent potential risks. The collaboration between academic medicine and industry has allowed for great advances in medicine in terms of drug, technology, and procedural developments. However, for-profit companies' interests may not align with those of academic universities. Companies tend to undertake research when the results of such work leads to company profits or enhances their reputation, and not solely for greater scientific understanding. In this article, the author reviews the types of conflicts of interest, the role of industry-sponsored trials, the adoption of new technologies from industry, and the role of industry with our medical society.
Keywords: conflict of interest; conflict of commitment; conflict of conscience; industry-sponsored trials; industrial relationships